Review on Relationship between Hypertension and Diabetes with their Medications - Park, Cheolin; Jung, Jaeeun (Asian Journal of Pharmaceutical Research and Development, 2025)
Hypertension and diabetes are two very common chronic conditions in the modern world, and they are closely related. Hypertension is a condition in which blood pressure is consistently high, and diabetes is a condition in which blood sugar levels are abnormally high. Both conditions increase the risk of cardiovascular disease, kidney disease, and many other complications. Studies have shown that many people with high blood pressure also have diabetes, and vice versa.In conclusion, hypertension and diabetes are interrelated conditions that can cause serious health problems for many people in the modern world. People with diabetes are more likely than the general population to develop high blood pressure because diabetes can cause damage to blood vessels or trigger an inflammatory response within the blood vessels, which can lead to stiffness of the blood vessels.Conversely, high blood pressure makes diabetes worse. When hypertension persists, the burden on the blood vessels continues to increase, putting the kidneys and heart of diabetics at greater risk.The bottom line is that these two conditions end up interacting with each other and promoting different complications.This approach will go a long way toward preventing the development of hypertension and diabetes and leading a healthy life.